Viewpoints on “the Other” - Adam Głaz (Ksiegarnia Akademicka Publishing, 2018)
Throughout his career of a reporter, writer, and “translator of cultures”, Ryszard Kapuściński was preoccupied with the notion of “the Other”. He synopsised his views in a collection of lectures published in 2006 as Ten Inny. It is instructive to look at how his portrayal of the Other (in Polish: Inny, but also Drugi/drugi or obcy) is rendered in Antonia Lloyd-Jones’ translation of the book into English (The Other, 2009), where the range of lexical choices includes Other, stranger, foreigner, and alien. Through lexical choices, both the author and the translator effect points of view in several senses of the term: (i) who is looking at whom, (ii) where (in the social sense) the observer and the observed are located, and (iii) how the other side is judged or evaluated. An additional level of complexity results from the system of articles in English (but not in Polish), which means that, e.g., the choice between the Other and an Other proves crucial for the construction of text-internal viewpoints. Thus, the author and the translator can not only actualise points of view, but are in fact coerced into semantic tensions that arise through sheer application of the lexico-grammatical inventories of the two languages.